2015
DOI: 10.1016/j.cub.2015.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Actin Age Orchestrates Myosin-5 and Myosin-6 Run Lengths

Abstract: Summary Unlike a static and immobile skeleton, the actin cytoskeleton is a highly dynamic network of filamentous actin (F-actin) polymers that continuously turn over. In addition to generating mechanical forces and sensing mechanical deformation, dynamic F-actin networks serve as cellular tracks for myosin motor traffic. However, much of our mechanistic understanding of processive myosins comes from in vitro studies where motility was studied on pre-assembled and artificially stabilized, static F-actin tracks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 37 publications
5
52
1
Order By: Relevance
“…It was further shown that not only the isoactin but also its age, determined by its nucleotide state, is involved in myosin sorting: The transporter myosin-5a has a longer run length on “young” actin which is the ADP·Pi state, concomitant with the site of actin polymerization at the plus-end at the cell periphery. Myosin-6, a minus-end directed motor takes longer runs on “old” actin in the ADP state, consistent with its movement to the center of the cell [138]. Sorting mechanism of the actin cytoskeleton result in regions that are enriched for actin signatures that either promote or exclude the interaction with a specific myosin class are cell type specific and dependent on cellular needs [139].…”
Section: Actin-linked Regulationmentioning
confidence: 99%
“…It was further shown that not only the isoactin but also its age, determined by its nucleotide state, is involved in myosin sorting: The transporter myosin-5a has a longer run length on “young” actin which is the ADP·Pi state, concomitant with the site of actin polymerization at the plus-end at the cell periphery. Myosin-6, a minus-end directed motor takes longer runs on “old” actin in the ADP state, consistent with its movement to the center of the cell [138]. Sorting mechanism of the actin cytoskeleton result in regions that are enriched for actin signatures that either promote or exclude the interaction with a specific myosin class are cell type specific and dependent on cellular needs [139].…”
Section: Actin-linked Regulationmentioning
confidence: 99%
“…Corrections for finite filament length and photobleaching need to be included, otherwise both interaction time and run length are underestimated (e.g. see Zimmermann et al [26]). Here, the systematic errors can be on the same order as the statistical error and therefore careful consideration of the evaluation method is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Although ATP-actin and ADP-Pi actin filaments have very similar properties, the ADP-actin accumulating at the minus-end of the filament is less rigid and stable. Interestingly, in vitro MYO5 shows increased run lengths on ADP+Pi-rich filaments, whereas MYO6 which prefers 'old' ADP-rich filaments [6]. Recent cryo-EM structures confirm minor conformational changes between nucleotide states of F-actin [84], as well as within the actin-binding interface of the motor domain of nonmuscle myosin class IIc (MYH14) and MYO6 [77,85].…”
Section: Actin Track Compositionmentioning
confidence: 99%